The hypertriglyceridemic rat as a genetic model of hypertension and diabetes - Stolba, P; Dobesová, Z; Husek, P; Opltová, H; Zicha, J; Vrána, A; Kunes, J (Life sciences, 1992)
Hypertriglyceridemia was demonstrated in untreated hypertensive patients as well as in animals with genetic and experimental hypertension. The main purpose of the present study was to evaluate the possibility to use the hereditary hypertriglyceridemic (HTG) nonobese rats in hypertensive research. Direct measurement of blood pressure demonstrated significantly higher systolic, diastolic and mean arterial pressures in HTG rats in comparison with control Wistar rats. There was significant positive correlation between blood pressure and plasma triglyceride concentration (r = 0.585, n = 40, p less than 0.001). In addition, there were significantly increased plasma norepinephrine and epinephrine concentrations in HTG rats, suggesting that the stimulation of sympathetic nervous system could be one of the pathogenetic mechanisms involved in the increase of blood pressure of HTG rats.
Keywords: hypertenze; Male; adrenalin; glukózový toleranční test; triglyceridy; Hyperlipoproteinemia Type IV; Glucose Tolerance Test; noradrenalin; Animals; tělesná hmotnost; Body Weight; modely genetické; Diabetes Mellitus; Epinephrine; krevní tlak; mužské pohlaví; krysa rodu Rattus; Norepinephrine; hyperlipoproteinemie typ IV; Blood Pressure; inzulin; modely nemocí na zvířatech; Rats; krevní glukóza; diabetes mellitus; Insulin; zvířata; Triglycerides; Hypertension; Blood Glucose; inbrední kmeny potkanů; Models, Genetic; Rats, Inbred Strains; Disease Models, Animal